Manhaj Muqtaroh Lita’lîm Al-Lughah Al-‘Arabiyyah Min Hilãli An-Nadhõir Al-Mukhõdi’ah Baina Al-Lughah Al-‘Arabiyah Wa Al-Lughah As-Sundãwiyah - Mursalin, Hisan (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
The curriculum is the basis of success for a student. Good teaching and learning outcomes depend on the curriculum that students learn at the school. Therefore this study aims to build a proposed curriculum for teaching Arabic, by considering the aspects that are followed in building the proposed curriculum, and the researcher uses a descriptive analytical approach and is applied in this study based on the analysis of words that are close to Arabic. , collecting information and data related to research, and then analyzing it to identify similarities seen from the vocabulary that approaches it or in other words, seen from the correlation. The study will yield important results, with the existence of a large number of similarities between Arabic and Sundanese in the Sundanese dictionary of Raden Satjadibrata, namely sixty-two words.